Phenomenology of Bioethics Technoethics and Lived-Experience - Ferrarello, Susi (The International Library of Bioethics, 2021)
This book offers a unique description of how phenomenology can help professionals from medical, environmental and social fields to explore notions such as interaffectivity, empathy, epoche, reduction, and intersubjective encounter. Written by a group of top scholars, it uniquely covers the relationship between phenomenology and bioethics, and focuses not only on medical cases, but also on the environment and emerging technologies. This variety of themes, whilst including techno-ethics, environmental ethics, animal ethics, and medical ethics, is conducive to appreciating broadly how phenomenology can improve our quality of our life. Despite its difficult themes, the book appeals to an audience of both academics and professionals who are willing to understand how to increase the quality of care in their professional field. Chapter 8 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com